EVALUATION OF VARIABLE AND META DATA SUITABILITY OF EMR AT EMERGENCY DEPARTMENT OF NUR HIDAYAH HOSPITAL - Intan Kurniawati; Rizka Dwi Yuliani; Agung Dwi Saputro (STIKES Syedza Saintika Padang, 2025)
Electronic Medical Records (EMR) require systems that meet compatibility and interoperability standards based on variable and metadata guidelines. Nur Hidayah Hospital has implemented EMR since 2022; however, it has not yet established a Standard Operating Procedure (SOP) related to this matter and has not fully referred to Minister of Health Decree (KMK) No. 1423 of 2022. This study aims to evaluate the conformity of EMR variables and metadata in the Emergency Department (ED).This is a qualitative descriptive study involving 4 informants and 1 triangulation subject. The object of the study is the ED's EMR, specifically the identity and triage forms. Data were collected through structured interviews and checklist-based observations. In the identity form, 81% of variables were compliant, 13% non-compliant, and 6% missing. In the triage form, 34% of variables were compliant, 3% non-compliant, and 63% missing. The factors contributing to non-conformity include lack of staff knowledge and the absence of SOPs. The EMR at Nur Hidayah Hospital is not yet fully aligned with KMK No. 1423 of 2022. Adjustments to variables and the addition of formats/values, especially in the identity and triage forms in the ED, are necessary.Keywords: Evaluation; Emergency Department; Electronic Medical Records; Variables and Metadata.